(3SQ GdaUGMIs - (3YHO Gddg Hf eMeO Hf SYjO Hf SfGf, CHh eMeO GdNaGLj GdMdHj,J (B466 (3g` s
(3ChdgG (B:s
(3GeG HYO aEfi deG QCjJ GdfGS eNJdajf ai eGgjI GdaUGMI hMbjbJgG ChOYJ cJGHi gPG WQakG ef TCfgG hLedI ef HjGfgG hbQHJ Pdc Ydi GdfGXQ hGhVMJg ddeJGed hde Ced HGdGNJUGQ Edi GdENdGd hdG eY GdESgGH Edi GdEedGd s
(3GdfSNI HgG MhGTs
(3aQZ ef JCdjag SfI (B454(3g`s
(3efbhdI ef fSNI cJHJ SfI (B455s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs